Further psychometric validation of the GAH scale: Responsiveness and effect size. Issue 3 (May 2017) - Cruz-Jentoft, Alfonso José; González, Bernardo; de la Rubia, Javier; Hernández Rivas, José Ángel; Soler, Juan Alfonso; Fernández Lago, Carlos; Arnao, Mario; Gironella, Mercedes; Pérez Persona, Ernesto; Zudaire, María Teresa; Olivier, Carmen; Altés, Alberto; et al.
Abstract: Objectives: The purpose of this study was to assess the responsiveness of the newly developed Geriatric Assessment in Hematology (GAH) scale to clinical change in older patients diagnosed with hematologic malignancies. Methods: A prospective observational study conducted in 164 patients aged ≥ 65 years and diagnosed with myelodysplastic syndrome (MDS)/acute myeloid leukemia (AML), multiple myeloma (MM), or chronic lymphocytic leukemia (CLL). Responsiveness of the GAH scales was studied by means of the Eastern Cooperative Oncology Group (ECOG) score, the Karnofsky performance status (KPS) score, the visual analog scale (VAS), and the physician's subjective assessment, used as clinical anchors to identify whether patients had changed clinically (either improved or worsened) or not since the baseline visit. Responsiveness was evaluated on the basis of effect size (ES). Results: 164 patients (men, 63.7%; median age, 77.0 (72.8–81.4) participated. Statistically significant correlations were obtained between the investigator's qualitative assessment and changes in ECOG, KPS, and VAS scores. Likewise, a statistically significant correlation was obtained between the investigator's qualitative assessment and changes in the GAH scale score. Responsiveness of the GAH scale to detect clinical change was satisfactory (ES 0.34). Conclusion: Findings confirm that the GAH scale is responsive to clinical changes in patients' health status. Additionally, the GAH scale is a promising tool to improve clinical decision-making in older patients with hematological malignancies.